2015
DOI: 10.1016/j.jbiomech.2014.11.012
|View full text |Cite
|
Sign up to set email alerts
|

High-bandwidth AFM-based rheology is a sensitive indicator of early cartilage aggrecan degradation relevant to mouse models of osteoarthritis

Abstract: Murine models of osteoarthritis (OA) and post-traumatic OA have been widely used to study the development and progression of these diseases using genetically engineered mouse strains along with surgical or biochemical interventions. However, due to the small size and thickness of murine cartilage, the relationship between mechanical properties, molecular structure and cartilage composition has not been well studied. We adapted a recently developed AFM-based nano-rheology system to probe the dynamic nanomechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
45
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 21 publications
7
45
0
Order By: Relevance
“…22 Recently, AFM-nanorheometric test showed that proteoglycan depletion results in >10-fold increase in murine cartilage hydraulic permeability, a deterministic factor of poroelasticity. 50 It is likely that besides modulus, other mechanical factors also undergo significant changes before the onset of PTOA. Our ongoing studies are using the custom AFM-nanorheometer 50 to probe into changes in the poroviscoelastic behaviors of cartilage after DMM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Recently, AFM-nanorheometric test showed that proteoglycan depletion results in >10-fold increase in murine cartilage hydraulic permeability, a deterministic factor of poroelasticity. 50 It is likely that besides modulus, other mechanical factors also undergo significant changes before the onset of PTOA. Our ongoing studies are using the custom AFM-nanorheometer 50 to probe into changes in the poroviscoelastic behaviors of cartilage after DMM.…”
Section: Discussionmentioning
confidence: 99%
“…50 It is likely that besides modulus, other mechanical factors also undergo significant changes before the onset of PTOA. Our ongoing studies are using the custom AFM-nanorheometer 50 to probe into changes in the poroviscoelastic behaviors of cartilage after DMM. Nevertheless, as shown by this study, E ind can adequately serve as a quantitative and sensitive indicator of PTOA (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, AFM-based nanomechanical tests on murine cartilage have become a valuable tool for investigating the articular cartilage biomechanical function and pathogenesis of OA (Batista et al, 2014; Nia et al, 2015; Stolz et al, 2009; Willard et al, 2014). The successful execution of AFM-based nanoindentation on murine cartilage demonstrated the potential of using similar approaches to provide valuable insights into the roles of meniscus in the development of OA.…”
Section: Discussionmentioning
confidence: 99%
“…Random binary sequence (RBS) displacements of amplitude in the range 8–12 nm (Fig. 1C) were then applied after the specimen had reached equilibrium (Nia et al, 2015a). To generate the RBS signal, we applied a low-pass filter and then a sign operator (sign(x) = 1 for x ≥ 0 and sign(x) = −1 for x < 0) to simulated white Gaussian noise.…”
Section: Methodsmentioning
confidence: 99%
“…A discrete Fourier transform was used to obtain the fundamental frequency component of the dynamic force F osc and displacement δ signals (Nia et al, 2013). The magnitude and phase of the dynamic complex indentation modulus at each frequency was obtained from the measured force and applied displacement amplitudes as previously described (Mahaffy et al, 2004; Nia et al, 2015a). The magnitude is: E(f)=Fitalicosc(f)δ(f)12(Rδ0)1/2 where R is the probe radius and δ 0 is the initial static offset indentation depth.…”
Section: Methodsmentioning
confidence: 99%